Phylogeny of Southeast Asian Mapania (Cyperaceae: Mapanioideae) using chloroplast sequence data - Zinnirah, Shabdin; José Ignacio, Márquez-Corro; Isabel, Larridon; David A., Simpson; Alastair, Culham (Oxford University Press, 2025)
Mapania (Cyperaceae) is a pantropical genus associated with the forest understorey. Its evolutionary history and species delimitation are poorly known in Southeast Asia. To address this lack of knowledge, DNA sequence data from four chloroplast regions (trnL-F, atpH-F, psbA-trnH, and trnK-matK) were generated for a number of populations of 15 species of Mapania. Bayesian and maximum likelihood analyses of the concatenated regions showed a better-resolved phylogeny than previous analyses based on morphological data alone. Mapania bancana was resolved as the sister to the other species of Mapania included in the study. Moreover, this study highlights the need for further investigation of the species limits in this genus. For instance, Mapania cuspidata is retrieved as polyphyletic, and a tentative new species has been detected closely related to Mapania debilis. This study also infers the cradle of the Southeast Asian Mapanias in Borneo, which also holds the largest diversity of the genus in the region. Mapania is still a poorly understood genus that requires further local taxonomic work and more comprehensive fieldwork records to better assess and protect these species.